A direct route to closo-SBCl thiaboranes from simple electron-precise synthons: the different role of chalcogen bonding in SB5Cl5 and SB11Cl11 crystals - Keller, Willi; Lissner, Falk; Ballmann, Joachim; Fanfrlík, Jindřich; Hnyk, Drahomír; Schleid, Thomas (Angewandte Chemie. International edition, 2024)
Six-vertex closo-SB5Cl5 (1) and ten-vertex closo-1-SB9Cl9 (2) thiaboranes have been prepared, besides the already known 12-vertex closo-SB11Cl11 (3), from the co-pyrolysis reaction of B2Cl4 with S2Cl2 at 280 °C in vacuo. The compounds are sublimable, off-white solids. Their elemental composition has been determined by high-resolution mass spectrometry. They were further characterized by one- and two-dimensional 11B NMR spectroscopy and X-ray structure determination for 1 and 3. Ab initio/GIAO/NMR computations support octahedral, bicapped square-antiprismatic, and icosahedral geometries for 1, 2 and 3, respectively, as expected based on their closo-electron counts. 1 is the first isolated example of a neutral polyhedral closo-thiaborane with a cluster size smaller than ten vertices. The solid-state structure of 3 is one of the rare examples of a single-crystal X-ray structure determination of an icosahedral heteroborane reported. The corresponding crystal-packing forces show the different role of chalcogen bonding in these octahedral and icosahedral crystals. In addition, there is a mass-spectrometry evidence for the recurrent formation of further thiaborane homologs of closo-SBnCln with n=4, 6, 10, and supra-icosahedral 12.
Gesehen am 29.04.2025